2021
DOI: 10.31234/osf.io/6xmzh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cheating in the wake of COVID-19: How dangerous is ad-hoc online testing for academic integrity?

Abstract: Worldwide, higher education institutions made quick and often unprepared shifts from on-site to online examination in 2020 due to the COVID-19 health crisis. This development sparked an ongoing debate on whether this development made it easier for students to cheat. We investigated whether students indeed cheated more often in online than in on-site exams and whether the use of online exams was also associated with higher rates of other behaviors deemed as academic dishonesty. To answer our research questions,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Although it has been argued that cheating might be easier in an online exam compared to on-campus exams (King & Case, 2014), students neither felt more tempted to cheat nor thought others cheated more. In line with a similar study in Germany, the reported levels of cheating were low (Janke et al, 2021), but contrary to their findings, no differences were found in the perceived levels of cheating in online versus offline exams. In addition, we did not find an effect of proctoring on perceived levels of cheating.…”
Section: Side-effects Of Proctoringsupporting
confidence: 79%
See 3 more Smart Citations
“…Although it has been argued that cheating might be easier in an online exam compared to on-campus exams (King & Case, 2014), students neither felt more tempted to cheat nor thought others cheated more. In line with a similar study in Germany, the reported levels of cheating were low (Janke et al, 2021), but contrary to their findings, no differences were found in the perceived levels of cheating in online versus offline exams. In addition, we did not find an effect of proctoring on perceived levels of cheating.…”
Section: Side-effects Of Proctoringsupporting
confidence: 79%
“…It is expected that these numbers are even higher for online exams, as both students and faculty argue that it is easier to cheat in online exams (King & Case, 2014;Rogers, 2006). A large survey among 1608 German students showed that although the frequency of self-reported cheating was relatively low, students reported cheating more in online exams (M = 2.22, SD = 1.71, on a scale from 1 to 7), compared with oncampus exams (M = 1.50, SD = 0.99; Janke et al, 2021). These findings from students' self-reports are further supported by other types of measures.…”
Section: Proctoring and Cheatingmentioning
confidence: 81%
See 2 more Smart Citations
“…The third question revealed the attitude to the correction of mistakes that had been made during the formative assessment. The feedback aspect proves to be a little more effective when the student and the teacher interact during the correction of mistakes process in the classroom rather than within the conditions of delayed-response communication in the Internet format (Janke et al, 2021).…”
Section: Discussionmentioning
confidence: 99%